Fast emitting nanocomposites for high-resolution ToF-PET imaging based on multicomponent scintillators - Orfano, Matteo; Pagano, Fiammetta; Mattei, Ilaria; Cova, Francesca; Secchi, Valeria; Bracco, Silvia; Rogers, Edith; Barbieri, Luca; Lorenzi, Roberto; Bizarri, Gregory; Auffray, Etiennette; Monguzzi, Angelo (Wiley, 2024)
Time-of-Flight Positron Emission Tomography (ToF-PET) is a medical imaging technique, based on the detection of two back-to-back γ-photons generated from radiotracers injected into the body. Its limit is the ability of employed scintillation detectors to discriminate in time the arrival of γ-pairs, that is, the coincidence time resolution (CTR). A CTR < 50 ps will enable fast imaging with ultralow radiotracer dose. Monolithic materials do not have simultaneously the required high light output and fast emission characteristics, thus the concept of scintillating heterostructure is proposed, where the device is made of a dense scintillator coupled to a fast-emitting light material. Here a composite polymeric scintillator loaded with hafnium oxide nanoparticles is presented. This enhanced by +300% its scintillation yield, by surpassing commercial plastic scintillators. The nanocomposite is coupled to bismuth germanate oxide (BGO) realizing a multilayer metascintillator. The energy sharing between its components is observed, which activates the nanocomposite's fast emission enabling a net CTR improvement of 25% with respect to monolithic BGO. These results demonstrate that a controlled loading with dense nanomaterials is an excellent strategy to enhance the performance of polymeric scintillators for their use in advanced radiation detection and imaging technologies.
Keywords: conjugated chromophores; energy sharing; multicomponent scintillators; nanocomposites; optical device; scintillation; ToF-PET